Using UHPLC–MS profiling for the discovery of new sponge-derived metabolites and anthelmintic screening of the NatureBank bromotyrosine library - Hayes, Sasha; Taki, Aya C.; Lum, Kah Yean; Byrne, Joseph J.; Ekins, Merrick G.; Gasser, Robin B.; Davis, Rohan A. (Beilstein Journal of Organic Chemistry, 2022)
In order to further expand the NatureBank open access compound library, chemical investigations of the Australian marine sponge, Ianthella basta, were undertaken since UHPLC–MS analysis of the extract from this sponge indicated the presence of a new alkaloid. Large-scale extraction and mass-directed isolation studies on the CH2Cl2/MeOH I. basta extract resulted in the purification of a new bromotyrosine-derived alkaloid, 5-debromopurealidin H (1), along with the known marine natural product, ianthesine E (2). The chemical structure of the new compound was determined following detailed spectroscopic and spectrometric data analysis. These two compounds (1 and 2) along with seven previously reported marine bromotyrosine alkaloids from the NatureBank open access library, which included psammaplysins F (3) and H (4), bastadins 4 (5), 8 (6) and 13 (7), aerothionin (8) and hexadellin A (9), were evaluated for their nematocidal activity against exsheathed third-stage larvae of Haemonchus contortus, a highly pathogenic parasite of ruminants. Of the nine compounds, bastadin 8 (6), hexadellin A (9) and bastadin 4 (5) showed inhibition towards larval motility after 72 h of exposure with IC50 values of 1.6 µM, 10.0 µM and 33.3 µM, respectively.
Keywords: alkaloid; anthelmintic; biodiscovery; bromotyrosine; 5-debromopurealidin H; Ianthella; NatureBank; sponge

MarinLit

(untitled) - Carroll, A. R.; Copp, B. R.; Davis, R. A.; Keyzers, R. A.; Prinsep, M. R. (Nat. Prod. Rep., 2022)

(untitled) - Moosa, B. A.; Sagar, S.; Li, S.; Esau, L.; Kaur, M.; Khashab, N. M. (Bioorg. Med. Chem. Lett., 2016)

The Alkaloids: Chemistry and Biology - Peng, J.; Li, J.; Hamann, M. T. (The Marine Bromotyrosine Derivatives, 2005)

(untitled) - Shaala, L. A.; Youssef, D. T. A.; Badr, J. M.; Sulaiman, M.; Khedr, A. (Mar. Drugs, 2015)

(untitled) - Sirimangkalakitti, N.; Yokoya, M.; Chamni, S.; Chanvorachote, P.; Plubrukrn, A.; Saito, N.; Suwanborirux, K. (Chem. Pharm. Bull., 2016)

(untitled) - Rotem, M.; Carmely, S.; Kashman, Y.; Loya, Y. (Tetrahedron, 1983)

(untitled) - Tsukamoto, S.; Kato, H.; Hirota, H.; Fusetani, N. (Tetrahedron, 1996)

(untitled) - Yang, X.; Davis, R. A.; Buchanan, M. S.; Duffy, S.; Avery, V. M.; Camp, D.; Quinn, R. J. (J. Nat. Prod., 2010)

(untitled) - Ichiba, T.; Scheuer, P. J.; Kelly-Borges, M. (J. Org. Chem., 1993)

(untitled) - Liu, S.; Fu, X.; Schmitz, F. J.; Kelly-Borges, M. (J. Nat. Prod., 1997)

NatureBank, Griffith Institute for Drug Discovery

The Australian Institute of Marine Science

(untitled) - Camp, D.; Davis, R. A.; Campitelli, M.; Ebdon, J.; Quinn, R. J. (J. Nat. Prod., 2012)

(untitled) - Kalaitzis, J. A.; de Almeida Leone, P.; Hooper, J. N. A.; Quinn, R. J. (Nat. Prod. Res., 2008)

Structure determination of organic compounds - Pretsch, E.; Bühlmann, P.; Affolter, C. (Summary Tables: Mass Spectrometry)

(untitled) - Davis, R. A. (J. Nat. Prod., 2005)

(untitled) - Davis, R. A.; Watters, D.; Healy, P. C. (Tetrahedron Lett., 2005)

(untitled) - Kobayashi, J.; Honma, K.; Tsuda, M.; Kosaka, T. (J. Nat. Prod., 1995)

(untitled) - Davis, R. A.; Carroll, A. R.; Pierens, G. K.; Quinn, R. J. (J. Nat. Prod., 1999)

(untitled) - Arabshahi, L.; Schmitz, F. J. (J. Org. Chem., 1987)

(untitled) - Taki, A. C.; Byrne, J. J.; Jabbar, A.; Lum, K. Y.; Hayes, S.; Addison, R. S.; Ramage, K. S.; Hofmann, A.; Ekins, M. G.; Wang, T.; Chang, B. C. H.; Davis, R. A.; et al. (Molecules, 2021)

(untitled) - Herath, H. M. D. P.; Preston, S.; Jabbar, A.; Garcia-Bustos, J.; Taki, A. C.; Addison, R. S.; Hayes, S.; Beattie, K. D.; McGee, S. L.; Martin, S. D.; Ekins, M. G.; Hooper, J. N. A.; et al. (Mar. Drugs, 2019)

(untitled) - Herath, H. M. P. D.; Preston, S.; Jabbar, A.; Garcia-Bustos, J.; Addison, R. S.; Hayes, S.; Rali, T.; Wang, T.; Koehler, A. V.; Chang, B. C. H.; Hofmann, A.; Davis, R. A.; et al. (Int. J. Parasitol.: Drugs Drug Resist., 2019)

(untitled) - Lum, K. Y.; Taki, A. C.; Gasser, R. B.; Tietjen, I.; Ekins, M. G.; White, J. M.; Addison, R. S.; Hayes, S.; St John, J.; Davis, R. A. (J. Nat. Prod., 2020)

(untitled) - Ramage, K. S.; Taki, A. C.; Lum, K. Y.; Hayes, S.; Byrne, J. J.; Wang, T.; Hofmann, A.; Ekins, M. G.; White, J. M.; Jabbar, A.; Davis, R. A.; Gasser, R. B. (Mar. Drugs, 2021)

(untitled) - Sallé, G.; Doyle, S. R.; Cortet, J.; Cabaret, J.; Berriman, M.; Holroyd, N.; Cotton, J. A. (Nat. Commun., 2019)

(untitled) - Xu, M.; Andrews, K. T.; Birrell, G. W.; Tran, T. L.; Camp, D.; Davis, R. A.; Quinn, R. J. (Bioorg. Med. Chem. Lett., 2011)

(untitled) - Butler, M. S.; Lim, T. K.; Capon, R. J.; Hammond, L. S. (Aust. J. Chem., 1991)

(untitled) - Moody, K.; Thomson, R. H.; Fattorusso, E.; Minale, L.; Sodano, G. (J. Chem. Soc., Perkin Trans. 1, 1972)

(untitled) - Okamoto, Y.; Ojika, M.; Kato, S.; Sakagami, Y. (Tetrahedron, 2000)

(untitled) - Ragini, K.; Fromont, J.; Piggott, A. M.; Karuso, P. (J. Nat. Prod., 2017)

(untitled) - Shaala, L. A.; Bamane, F. H.; Badr, J. M.; Youssef, D. T. A. (J. Nat. Prod., 2011)

(untitled) - Tintillier, F.; Moriou, C.; Petek, S.; Fauchon, M.; Hellio, C.; Saulnier, D.; Ekins, M.; Hooper, J. N. A.; Al-Mourabit, A.; Debitus, C. (Mar. Drugs, 2020)

(untitled) - Gómez-archila, L. G.; Zapata, W.; Galeano, E.; Martínez, A.; Rugeles, M. T. (Vitae, 2014)

(untitled) - Galeano, E.; Thomas, O. P.; Robledo, S.; Munoz, D.; Martinez, A. (Mar. Drugs, 2011)

(untitled) - Lee, Y.-J.; Han, S.; Lee, H.-S.; Kang, J. S.; Yun, J.; Sim, C. J.; Shin, H. J.; Lee, J. S. (J. Nat. Prod., 2013)

(untitled) - Kumar, R.; Bidgood, C. L.; Levrier, C.; Gunter, J. H.; Nelson, C. C.; Sadowski, M. C.; Davis, R. A. (J. Nat. Prod., 2020)

(untitled) - Miao, S.; Andersen, R. J.; Allen, T. M. (J. Nat. Prod., 1990)

(untitled) - Shinde, P. B.; Lee, Y. M.; Dang, H. T.; Hong, J.; Lee, C.-O.; Jung, J. H. (Bioorg. Med. Chem. Lett., 2008)

(untitled) - Bhat, C.; Ilina, P.; Tilli, I.; Voráčová, M.; Bruun, T.; Barba, V.; Hribernik, N.; Lillsunde, K.-E.; Mäki-Lohiluoma, E.; Rüffer, T.; Lang, H.; Yli-Kauhaluoma, J.; et al. (Mar. Drugs, 2018)

(untitled) - Encarnación-Dimayuga, R.; Ramírez, M. R.; Luna-Herrera, J. (Pharm. Biol. (Abingdon, U. K.), 2003)

(untitled) - Drechsel, A.; Helm, J.; Ehrlich, H.; Pantovic, S.; Bornstein, S. R.; Bechmann, N. (Mar. Drugs, 2020)

(untitled) - Thompson, J. E.; Walker, R. P.; Faulkner, D. J. (Mar. Biol. (Heidelberg, Ger.), 1985)

(untitled) - Taki, A. C.; Byrne, J. J.; Wang, T.; Sleebs, B. E.; Nguyen, N.; Hall, R. S.; Korhonen, P. K.; Chang, B. C. H.; Jackson, P.; Jabbar, A.; Gasser, R. B. (Pharmaceuticals, 2021)